Gambaran Darah sebagai Indikator Kesehatan Ikan Nila (Oreochromis niloticus) yang Diberi Pakan Tambahan Probiotik Rabbal - Maulinia Maulinia; Sri Herlina (Fakultas Peternakan Universitas Kristen Palangka Raya, 2022)
The purpose of this study is to find out how the blood picture of tilapia that is fed with the addition of probiotic rabal and to find out what the values of erythrocytes, leukocytes, hemoglobin, and hematocrit of tilapia are fed with the addition of probiotic rabal. The research was conducted for 21 days in May - July 2021. The analytical method used for the research of tilapia health indicators was carried out descriptively. The result data obtained and analyzed are hematological parameters which include hemoglobin levels, hematocrit levels, red blood cell values (erythrocytes) and white blood cell values (leukocytes) as well as supporting data such as water quality. The data is presented in tabular form which is then discussed descriptively with a related literature approach based on the results of previous studies. The research variables were calculating hemoglobin levels, hematocrit levels, erythrocyte values and leukocyte values of tilapia (Oreochromis niloticus). From the results of the study for 3 times the observation of blood picture observations in tilapia fed with added probiotic rabbal. The addition of rabal probiotics to tilapia feed can increase the number of red blood cells ranging from 3.10 x 106/mm - 3.5 x 106/mm, white blood cells 33.240 cells/mm3 - 39,540 cells/mm3, hemoglobin ranging from 8.2% - 10.2%, and the hematocrit ranged from 38.3% to 42.3%. In tilapia compared before being given additional feed with rabal probiotics. Keywords: Blood picture, probiotic, Oreochromis niloticus